TRANSFORMATION OF ADAT VILLAGE POST ENACTMENT OF LAW NO. 6 YEAR 2014 ON VILLAGE: A GOVERNANCE PERSPECTIVE (STUDY IN KARO REGENCY) - Erna Herlinda; M Maria; Rosnidar Sembiring (Jurnal Dinamika Hukum, 2018)
The determination of an adat community become adat village results in implementing one function, governmental function. It is the adat village governance that will fulfill a village authority based on the rights of origin. This research aims to identify the development and transformation of the adat village governance in Karo Regency. This is an empirical law research with a qualitative analysis. Data is collected from both literature study and field study by carrying out an observation and comprehensive interviews. The result shows that management and implementation of adat village governance are done in accordance with rights of origin and adat law. Aside from a Village Head, a Turpuk (adat Head) is also recognized. According to agreed regulations, a Village Head must also be a Turpuk. It means the Turpuk must have a surname of Simanjorang or Munthe which is regarded as a descendant of the village (huta) founder. In carrying out its governance, the Village Head must involve the Turpuk. This regulation has been applied prior to the ratification of Article Number 6 Year 2014 on Villages till present. Keywords: adat village, governance, transformation